Homogeneous and polymorphic transformations to ordered intermetallics in nanostructured Au–Cu multilayer thin films - Singh A.; Pradeepkumar M.S.; Jarwal D.K.; Jit S.; Bysakh S.; Ahmad M.I.; Basu J.; Mandal R.K. (My University, 2025)
Abstract: Atomic arrangements in the nanostructured grains and interfaces of thermally evaporated Au/Cu multilayer thin films on polycrystalline Si substrate have been explored through GIXRD, HRTEM, simulation, and direct structure imaging. GIXRD pattern conforms to cF4 solid solution of Au and Cu with peak broadening and shift. Comparative analysis with simulation indicated the presence of cP4, tP4, oP8, and oI40 phases in the multilayer. The Cu layer is amorphous. Localized amorphous phase forms at the Cu–Si interface due to the impingement of Cu atoms during deposition. Interfaces of Au–Cu are wavy. The Au layer is polycrystalline and columnar with some twin-like defects present in them. At the Cu–Au interface, diffusionally grown cP4, tP4, oI40, and oP8 phases could be observed. Adatom mobility, concurrent growth, and coalescence of growth islands lead to columnar growth. Ordered intermetallic phases could be related with the cF4 solid solution phase through polymorphism. The strain associated with the polymorphs and the solid solution phase is quite small. Faceted semi-coherent interfaces of the ordered phases with the solid solution phase have been resolved. The ordered phases grow into the solid solution matrix by homogeneous transformation. Structure imaging of the ordered phases indicated that most of the time a cluster of atoms is imaged in these structures. The interfaces are likely to be chemically diffused in nature. Polymorphism and homogeneous nature of the transformation at low temperature allows local transformation to ordered phases, that explain the phase field ambiguity in the binary phase diagram. Such structural details are critical in understanding the novel properties in these nanostructured alloys. Graphical abstract: [Figure not available: see fulltext.]. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.